The impact of pension system reform on projected old-age income: The case of Poland - Elena Jarocinska; Anna Ruzik-Sierdzińska (Center for Social and Economic Research (CASE), 2016)
This paper analyses the distributional effects of the Polish old-age pension reform introduced in 1999. Following a benchmark Mincer earnings equation, and using a newly developed microsimulation model we project future pension benefits for males born in years 1969-1979. We find that inequality of predicted first pension benefits measured by the Gini coefficient increases from 0.119 to 0.165 for cohorts of men retiring between 2036 and 2046. The observed increased inequality of pension benefits is due to the decreasing share of initial capital that is based on a more generous DB formula in the total accumulated pension capital. At the same time, inequality in replacements rates decreases due to a stronger link between contributions paid through the entire working life and pension benefits.
Keywords: H55; J26; 330; pension benefits; inequality; replacement rates; microsimulation